Osmotic adjustment and hormonal regulation of stomatal responses to vapour pressure deficit in sunflower. Issue 4 (19th June 2020) - Cardoso, Amanda A; Brodribb, Timothy J; Kane, Cade N; DaMatta, Fábio M; McAdam, Scott A M
Abstract: Dynamic variation of the stomatal pore in response to changes in leaf–air vapour pressure difference (VPD) constitutes a critical regulation of daytime gas exchange. The stomatal response to VPD has been associated with both foliage abscisic acid (ABA) and leaf water potential (Ψ  l ); however, causation remains a matter of debate. Here, we seek to separate hydraulic and hormonal control of stomatal aperture by manipulating the osmotic potential of sunflower leaves. In addition, we test whether stomatal responses to VPD in an ABA-deficient mutant ( w-1 ) of sunflower are similar to the wild type. Stomatal apertures during VPD transitions were closely linked with foliage ABA levels in sunflower plants with contrasting osmotic potentials. In addition, we observed that the inability to synthesize ABA at high VPD in w-1 plants was associated with no dynamic or steady-state stomatal response to VPD. These results for sunflower are consistent with a hormonal, ABA-mediated stomatal responses to VPD rather than a hydraulic-driven stomatal response to VPD. Abstract : In sunflower a plant hormone called abscisic acid closes the microscopic pores on the leaves to prevent excessive water loss when humidity decreases.